Kegel Exercises On Urinary Incontinence - Aniska Indah Fari; Veroneka Yosepfha Windahandayani (Jurnal Ilmu Kesehatan dan Gizi, 2023)
One of the decline in body systems experienced by adult women is the urinary system. In an adult woman, the decrease in the hormone estrogen causes atrophy of the urethral tissue and the effects of childbirth cause weakness of the pelvic floor muscles which can lead to disturbances in controlling urine output, which is called urinary incontinence. The impact of urinary incontinence is experiencing irritation in the area around the vagina, feeling embarrassed, withdrawing from the environment and can lead to depression. Efforts that can be made to overcome urinary incontinence include non-pharmacological therapy in the form of Kegel exercises. The purpose of this study was to determine the level of urinary incontinence before and after being given Kegel exercises. This study uses a quantitative method with a Quasi Experimental design with a Pre-post test approach to Non-equivalent Control Group, the sample in this study amounted to 39 respondents with a sampling technique using purposive sampling. The results of this study showed that the average level of mild urinary incontinence in pre-test women in the intervention group I was 12 people (60%) and post-test was 15 people (75%) then 5 people were normal (25%). While the level of mild urinary incontinence in pre-test women in the intervention group II was 9 people (47.4%) and at the post-test as many as 16 people (84.2%) then found normal as many as 3 people (15.8% )